Acne-specific quality of life questionnaire (Acne-QoL): translation, cultural adaptation and validation into Brazilian-Portuguese language - Cristhine de Souza Leao Kamamoto; Karime Marques Hassun; Edileia Bagatin; Jane Tomimori (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: many studies about the psychosocial impact of acne have been reported in international medical literature describing quality of life as a relevant clinical outcome. It is well known that the patient's perception about the disease may be different from the physician's evaluation. Therefore, it is important to use validated instruments that turn the patient's subjective opinion into objective information. OBJECTIVES: to translate into Brazilian-Portuguese language and to culturally adapt a quality of life questionnaire, the Acne-Specific Quality of Life Questionnaire (Acne-QoL), as well as to evaluate its reliability and validity. METHODS: measurement properties were assessed: 1) validity: comparison between severity and Acne-QoL domain scores, correlations between acne duration and Acne-QoL domain scores, and correlation between Acne-QoL domain scores and SF-36 components; 2) internal consistency: Cronbach's α coefficient; 3) test-retest reproducibility: intraclass correlation coefficient and Wilcoxon test. RESULTS: Eighty subjects with a mean age of 20.5 ± 4.8 years presenting mild (33.8%), moderate (36.2%) and severe (30%) facial acne were enrolled. Acne-QoL domain scores were similar among the different acne severity groups except for role-social domain. Subjects with shorter acne duration presented significant higher scores. Acne-QoL domains showed significant correlations, both between themselves and with SF-36 role-social and mental health components. Internal consistency (0.925-0.952) and test-retest reproducibility were considered acceptable (0.768-0.836). CONCLUSIONS: the Brazilian-Portuguese version of the Acne-QoL is a reliable and valid satisfactory outcome measure to be used in facial acne studies.